KAJIAN KESIAPAN (E-READINESS) KECAMATAN DALAM PENERAPAN E-GOVERNMENT KOTA SEMARANG - Suwito Eko Pramono (Badan Perencanaan Pembangunan Daerah Kota Semarang, 2021)
The climate of Semarang that caracterized by dry and hot temperature,low humidity causes the use of air conditioning system in the residential building to obtain indoor thermal comfort. The rise of electricity rate will give a significant effect to the society, the strategy of domestic electricity consumption to be more effeicient is needed. The Government must make a policy as the Goverment Goodwill to realize the attention of electricity consumption efficiency as the experience of the neighbouring country, Malaysia. The efficiency of elecricity consumption was applied in the vision of City in the Garden. It is the government obligation to exemplify the pattern of energi saving to solve the issueof energi crisis. Related previous studies proved building design caused a squanderring of electricity consumption that harmed the environment. One of environmental friendly elements on building design is the application of greenwall.The initial experiment of this study carried out by creeping the plant up the wall of building model. The temperatur of building walls was hourly measured along the day. The result of this study found that creeped plant up the wall building decrease 20C of the indoor temperature. The application of greenwall showed the indoor temperature was lower the outdoor. The second result found that the decrease of indoor temperature was also influence by the planted area. The most effective place of the planted area is in middle of vertical wall.